Protección Biológica del talud junto al canal de riego Belisario Quevedo con dos especies arbóreas (Acacia melanoxylonen), (Alnus acuminata), y una especie arbustiva (Murraya paniculata), en la Parroquia Belisario Quevedo, Cantón Latacunga, 2022. - Patín Guaquipana, Gerardo Oswaldo (2022)
In the present research work, the general objective was to analyze the behavior of two tree species (Acacia melanoxylonen), (Alnus acuminata), and a shrub species (Murraya paniculata), in the protection of the slope next to the Belisario Quevedo irrigation channel of the canton. Latacunga. The methodology used was based on the application of bibliographical and descriptive research towards the application of the inductive - deductive method with the purpose of starting from general information to particular information in order to achieve the fulfillment of the proposed objectives. The evaluation of the behavior of the planted species with respect to mortality, it was possible to determine that there was a mortality of 25% of the alder, 28% of the Black Acacia and 15% of the Indian Orange Blossom. While the percentage of adaptation of the Alder was 75%, of the Black Acacia 72% and 85% of the Indian Orange Blossom. With respect to the height of the Alder and the Black Acacia they presented a height of 0.52 cm., and a width of the cup of 0.15 cm., in relation to the Azahar it presented a height of 0.70 cm., and an average of 0.26 cm during the 300 days after the trial, determining that each of the species grow based on the morphological characteristics of each of them, being able to establish that the species grow around 1 cm., for 30 days. Being able to conclude that each of the species play an important role in the prevention of mass movements, reducing the impact generated by rainwater drops and therefore reduce the speed of water produced by precipitation that occurs in the place, guaranteeing slope maintenance.